Manufacturing process of ultrathin extruded nylon sheath power cable
Patent Information
- Application Number
- CN202611164606.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-10-13
AI Technical Summary
然而,将尼龙以超薄形式(厚度通常不足一毫米)挤包于电缆外层时,面临着突出的工艺挑战
本发明获得了一种超薄挤出尼龙护层电力电缆生产制造工艺,在材料层面,通过对聚烯烃进行环氧官能团接枝改性,显著提升了护层材料与尼龙外护层之间的界面相容性及低温抗冲击韧性;在结构层面,陶瓷硅橡胶耐火层与超薄尼龙护套的协同配合,使电缆兼具优异的耐火安全性和轻量化紧凑结构,同时环保填充层和包带设计有效缓冲了绝缘内芯的绞合应力,保障了缆芯圆整度;在工艺层面,采用梯度温水冷却方式对挤出护层进行逐级定型,能够有效释放成型内应力并细化结晶组织,从而消除超薄护层常见的收缩变形和微裂纹隐患,大幅提升了成品质量一致性和长期使用可靠性,适合规模化连续生产。
Smart Images

Figure CN122907427A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of power cable manufacturing technology, specifically relating to a manufacturing process for ultra-thin extruded nylon sheath power cables. Background Technology
[0002] With the rapid advancement of modern urbanization and the booming development of the new energy industry, the application scenarios of power cables, as a key carrier of electrical energy transmission, are becoming increasingly complex. In densely laid applications such as rail transit, high-rise buildings, ships, and electric vehicle charging facilities, cables are required not only to have excellent electrical insulation performance and flame-retardant fire resistance, but also to meet more stringent requirements for lightweighting and miniaturization in terms of outer diameter, bending radius, and overall weight. Traditional power cables typically use polyvinyl chloride or polyethylene as the outer sheath material. Although the processing is mature and the cost is low, their mechanical strength and abrasion resistance are relatively limited. To meet the tensile, compressive, and rodent- and termite-proof requirements in specific environments, it is often necessary to increase the sheath thickness or add multi-layer composite structures. This directly leads to an increase in the cable's outer diameter and weight per unit length, which is not conducive to installation and layout in limited spaces or long-distance suspended installation.
[0003] Nylon, with its excellent mechanical strength, superior abrasion resistance, good oil and solvent resistance, and low coefficient of friction, is considered an ideal thin-layer protective material to replace traditional thick-walled sheaths. However, extruding nylon into the outer layer of cables in an ultra-thin form (typically less than one millimeter thick) presents significant technological challenges. On the one hand, the melt viscosity of nylon is extremely sensitive to temperature changes, and the processing window is narrow. If the cooling method is improper, the ultra-thin nylon layer is prone to shrinkage and warping, interlayer debonding, or orange peel defects due to uneven crystallization, severely affecting the appearance quality and sealing performance of the sheath. On the other hand, nylon and the underlying polyolefin sheath material have significant differences in chemical polarity, resulting in insufficient interfacial bonding strength. Under repeated bending or alternating high and low temperature conditions, delamination is likely to occur, thereby weakening the overall mechanical protection performance.
[0004] Furthermore, the safety of cables under extreme conditions such as fires cannot be ignored. Existing conventional fire-resistant layers mostly employ mica tape wrapping structures, which provide some fire and heat insulation, but the overlap rate is difficult to control precisely, and the mica tape is prone to embrittlement and detachment at high temperatures, leading to unstable fire-resistant integrity. Ceramicized silicone rubber, as a novel fire-resistant material, can rapidly sinter into a hard ceramic-like shell under high-temperature flame erosion, effectively preventing the spread of flames to the inner insulation layer. However, how to efficiently integrate it with the various layers of the cable structure and achieve continuous and stable production remains a pressing technical challenge in this field.
[0005] In view of the above situation, the present invention aims to provide a manufacturing process for ultra-thin extruded nylon sheath power cables. Through the synergistic innovation of material modification, structural optimization and cooling and shaping processes, the quality bottlenecks of ultra-thin nylon sheath extrusion molding and interface bonding are overcome. At the same time, the fire resistance and low temperature toughness of the cable are comprehensively improved to meet the urgent needs of modern high-end equipment for high-performance and compact power cables. Summary of the Invention
[0006] The purpose of this invention is to provide a manufacturing process for an ultra-thin extruded nylon sheath power cable, which has good tensile properties and low-temperature impact toughness.
[0007] The technical solution adopted by the present invention to achieve the above objectives is as follows: An ultra-thin extruded nylon sheathed power cable includes four insulated cores. Each insulated core comprises, from the inside out, a conductor, a fire-resistant layer, and an insulation layer. The insulated cores are embedded in an environmentally friendly filler material layer. A cabling wrapping layer is wrapped around the insulated cores and the environmentally friendly filler material layer. The cabling wrapping layer is covered, from the inside out, with an inner lining layer, an armor layer, an outer sheath layer one, and an outer sheath layer two.
[0008] For the purposes of this invention, the conductor is selected from one of copper core conductor, aluminum core conductor, or aluminum alloy core conductor; For the purposes of this invention, the aforementioned refractory layer comprises a ceramic silicone rubber refractory layer; the aforementioned ceramic silicone rubber refractory layer is prepared by melting, extruding, and vulcanizing ceramic silicone rubber granules, followed by cooling and shaping.
[0009] For the purposes of this invention, the aforementioned insulating layer is selected from either a polyvinyl chloride insulating layer or a cross-linked polyethylene insulating layer; For the purposes of this invention, both the inner liner and the outer sheath are selected from either a polyolefin sheath or a modified polyolefin sheath; the modified polyolefin sheath is prepared by melt extrusion of modified polyolefin granules followed by cooling and shaping. For the purposes of this invention, the aforementioned armor layer comprises a steel strip armor layer; For the purposes of this invention, the outer protective layer two comprises an ultra-thin nylon sheath.
[0010] Specifically, the method for preparing the above-mentioned ultra-thin extruded nylon sheath power cable includes: Step 1: Preheat the conductor to 60-90℃ for 20-30 minutes, then feed it into the extruder head. Add ceramic silicone rubber granules into the extruder. The processing temperature of the extruder chamber is: Zone 1 45-55℃, Zone 2 60-75℃, Zone 3 80-85℃. The processing temperature of the extruder head is: Zone 4 75-80℃, Zone 5 80-85℃. Then extrude the granules onto the conductor and immediately feed them into the hot air vulcanization tunnel. Hold the tube at 115-125℃ for 25-35 seconds, at 155-165℃ for 45-55 seconds, and at 195-205℃ for 15-25 seconds. Finally, cool and shape the tube with a three-stage warm water cooling process to obtain the conductor with a refractory coating. Step 2: Treat polyvinyl chloride or cross-linked polyethylene granules at 65-70℃ for 3-4 hours, then add them to an extruder and extrude them onto the refractory layer. Finally, cool and shape them in three stages with warm water to obtain the insulating core. Step 3: Twist the four insulating cores together, wrap the twisted insulating cores with aramid braided fabric to form a cable wrapping layer, and then fill the space between the insulating cores and the cable wrapping layer with a mixture of alkali-free glass fiber yarn and flame-retardant polypropylene filler rope to form an environmentally friendly filler material layer. Step 4: The inner lining layer is made by drying polyolefin or modified polyolefin granules at 65-75℃ for 4-6 hours, and then adding the granules into an extruder. The milling temperatures are: Zone 1 155-165℃, Zone 2 175-185℃, Zone 3 188-192℃, Zone 4 198-202℃, Zone 5 208-212℃; the flange zone 6 temperature is 208-212℃; and the die head processing temperatures are: Zone 7 218-222℃, Zone 8 228-233℃, Zone 9 228-233℃, Zone 10 228-233℃. The lining is then extruded onto the cable wrapping layer and shaped using segmented warm water cooling. Step 5: Wrap at least two layers of galvanized steel strip around the inner lining layer to form a steel strip armor layer. Then, dry the polyolefin or modified polyolefin granules at a temperature of 65-75℃ for 4-6 hours. Then, add the granules to the extruder. The processing temperature of the extruder chamber is: Zone 1 155-165℃, Zone 2 175-185℃, Zone 3 188-192℃, Zone 4 198-202℃, Zone 5 208-212℃. The flange zone 6 temperature is 208-212℃. The die head processing temperature is: Zone 7 218-222℃, Zone 8 228-233℃, Zone 9 228-233℃, Zone 10 228-233℃. Extrude the material onto the armor layer and then cool it in three stages with warm water. The traction speed of the entire cooling line is uniform, with a speed range of 10-20m / min. Step Six: Dry the nylon granules at 80-105℃ and 0.05-0.1MPa vacuum for 4-6 hours; then add the granules to an SJ-120 or SJ-150 extruder with a length-to-diameter ratio of 20:1-25:1 and a compression ratio of 3.5:1-4:1. The milling temperatures are: Zone 1 234-236℃, Zone 2 239-241℃, Zone 3 239-241℃, Zone 4 244-241℃. The temperature ranges from 6℃ in zone 5 to 244-246℃ in zone 6, and from 249-251℃ in zone 7 of the flange. The processing temperature of the die head is 254-256℃ in zone 8, 254-256℃ in zone 9, 254-256℃ in zone 10, and 254-256℃ in zone 11. After being extruded onto the outer sheath, the cable passes through a 0.5-1.5m air-cooling section, followed by a three-stage warm water cooling and shaping process to produce an ultra-thin extruded nylon sheath power cable.
[0011] During the melt extrusion process of the ultra-thin nylon sheath, the nylon molecular chains are fully plasticized in the high-temperature die chamber and highly oriented along the traction direction. After extrusion through the die, it immediately enters the gradient warm water cooling zone. This cooling method allows the sheath to solidify gradually from the outside to the inside. The outer layer first forms a dense skin, suppressing the large number of spherulites and shrinkage pores generated by rapid cooling of the internal melt; subsequently, the inner layer molecular chains are orderly stacked and complete secondary crystallization under the relatively gentle temperature difference driving force. This process retains the inherent high tensile strength and abrasion resistance of nylon, and releases the molding internal stress through the uniform and refined grain structure, thus endowing the ultra-thin sheath, only a few tenths of a millimeter thick, with excellent interfacial bonding, crack resistance, and overall dimensional stability, ensuring the integrity of the sheath structure under bending or thermal cycling conditions.
[0012] For the purposes of this invention, the conductor diameter is 1.13-34 mm, the fire-resistant layer thickness is 0.1-0.16 mm, the insulation layer thickness is 0.7-3 mm, the cable wrapping layer thickness is 0.1-0.18 mm, the inner lining layer thickness is 1-2 mm, the armor layer thickness is 0.2-0.8 mm, the outer sheath one thickness is 1.4-3 mm, and the outer sheath two thickness is 0.3-0.6 mm.
[0013] For the purposes of this invention, the mass ratio of the alkali-free glass fiber yarn to the flame-retardant polypropylene filler rope in the above-mentioned mixture of alkali-free glass fiber yarn and flame-retardant polypropylene filler rope is 1:1.4-1.6.
[0014] For the present invention, the above-mentioned three-stage warm water cooling is as follows: the first stage cooling water temperature is 60-80℃, the second stage cooling water temperature is 40-50℃, and the third stage cooling water temperature is 20-30℃.
[0015] For the present invention, the extruder described above needs to be preheated to the set temperature for 2-2.5 hours before adding the granules.
[0016] This invention also discloses a method for preparing ceramic silicone rubber granules, comprising: Add methyl vinyl silicone rubber to a Banbury mixer and mix in a closed system at 65-75°C for 2-3 minutes. Then add hydroxyl silicone oil, silane coupling agent, and zinc borate, and continue mixing for 2-4 minutes. Add mica powder, kaolin, hydrophobic fumed silica, and glass powder in three batches, with an interval of 3-5 minutes between each batch. Raise the temperature to 140-160°C and degas under vacuum at -0.07MPa to -0.09MPa for 20-30 minutes. Then add the mixture to an open mill. In the machine, pass through the thin tube 3-5 times, and after cooling to room temperature, add 2,4-dichlorobenzoyl peroxide and knead for 10-15 minutes. Adjust the roller gap to 1-1.5 mm and continuously produce flat rubber sheets. Lay the rubber sheets flat and let them stand at room temperature for 3-5 hours to mature. Then cut them into strips and send them into a twin-screw granulator. The temperature is 55-65℃ in zone 1, 68-72℃ in zone 2, 74-76℃ in zone 3, and 69-71℃ at the die head. After extrusion, cool with water at 20-25℃ to shape and pelletize to obtain ceramic silicone rubber granules.
[0017] During the mixing and preparation of ceramic silicone rubber granules, the methyl vinyl silicone rubber matrix gradually softens under the shear force of the internal mixer and encapsulates various functional fillers. The surface of the hydrophobic fumed silica is rich in silanol groups, which form physical-chemical dual crosslinking points with the vinyl side groups and hydroxyl silicone oil on the silicone rubber molecular chain through hydrogen bonding and condensation reactions, significantly enhancing the reinforcing effect. Muscovite powder, kaolin, and glass powder, as precursors for the ceramic skeleton, are uniformly dispersed in the matrix during high-temperature mixing, synergistically constructing a potential ceramic reaction interface with zinc borate. The subsequently added organic peroxide, 2,4-dichlorobenzoyl peroxide, is uniformly penetrated during the open mill refining stage and uniformly adsorbed onto the filler surface after static curing. During granulation and extrusion, the peroxide is uniformly dispersed within the system, laying a uniform activation foundation for the rapid initiation of free radical crosslinking reactions in the hot air drying tunnel during the subsequent vulcanization stage, ensuring the orderly connection between the refractory layer vulcanization crosslinking network and the ceramic conversion process.
[0018] For the purposes of this invention, the above-mentioned ceramic silicone rubber material, by weight, comprises: 95-105 parts methyl vinyl silicone rubber, 30-50 parts mica powder, 20-40 parts kaolin, 25-30 parts hydrophobic fumed silica, 3-5 parts hydroxyl silicone oil, 0.6-1 parts silane coupling agent, 28-32 parts glass powder, 1-1.4 parts 2,4-dichlorobenzoyl peroxide, and 4-6 parts zinc borate.
[0019] This invention also discloses a method for preparing modified polyolefin granules, comprising: The polyolefin granules were dried at 28-35℃ for 2.5-4 hours and then fed into a twin-screw extruder. 1,2-epoxy-4-vinylcyclohexane and diisopropylbenzene peroxide were mixed evenly and then added to the polyolefin granules for melt grafting reaction. The temperature of zone 1 was 70-75℃, zone 2 was 115-125℃, zone 3 was 115-125℃, the die head temperature was 138-145℃, and the screw speed was 130-140 r / min. After the extrudate was cooled in a cooling water tank, it was pelletized and then subjected to Soxhlet extraction for 20-24 hours. After vacuum drying, the modified polyolefin granules were obtained.
[0020] In the melt grafting preparation process of modified polyolefin granules disclosed in this invention, the polyolefin matrix is completely melted and plasticized in the high-temperature shear section of a twin-screw extruder. Dicumyl peroxide decomposes upon heating to generate primary free radicals, which rapidly capture tertiary hydrocarbon atoms from the polyolefin molecular chain, forming stable macromolecular free radical active centers at the chain ends or side groups. Subsequently, the 1,2-epoxy-4-vinylcyclohexane monomer, due to the high reactivity of its vinyl double bond, preferentially undergoes an addition coupling reaction with the macromolecular free radicals, thereby grafting onto the polyolefin backbone via chemical bonds and introducing epoxy functional groups into the side chains. After extrusion granulation, unreacted monomers and residual initiator decomposition byproducts are thoroughly removed by Soxhlet extraction, and vacuum drying ensures the final product is pure and free of low-molecular-weight volatiles. This method achieves the effective chemical introduction of polar functional groups into the polyolefin material. Furthermore, the polar groups of the modified polyolefin promote interfacial wetting at the nylon extrusion temperature, while gradient cooling matches the nylon crystallization shrinkage stress with the thermal expansion of the underlying layer, jointly preventing interlayer delamination.
[0021] For the purposes of this invention, the mass ratio of the above-mentioned polyolefin granules to 1,2-epoxy-4-vinylcyclohexane is 1:0.1-0.15; the mass ratio of the polyolefin granules to dicumyl peroxide is 1:0.008-0.013.
[0022] The beneficial effects of this invention include: This invention provides a manufacturing process for ultra-thin extruded nylon sheath power cables. At the material level, epoxy functional group grafting modification of polyolefin significantly improves the interfacial compatibility and low-temperature impact toughness between the sheath material and the nylon outer sheath. At the structural level, the synergistic cooperation between the ceramic silicone rubber fire-resistant layer and the ultra-thin nylon sheath enables the cable to possess both excellent fire resistance and a lightweight, compact structure. Simultaneously, the environmentally friendly filler layer and wrapping tape design effectively buffer the stranding stress of the insulation core, ensuring the roundness of the cable core. At the process level, a gradient hot water cooling method is used to progressively shape the extruded sheath, effectively releasing molding internal stress and refining the crystalline structure. This eliminates the common shrinkage deformation and micro-crack hazards of ultra-thin sheaths, significantly improving the consistency of finished product quality and long-term reliability, making it suitable for large-scale continuous production. Attached Figure Description
[0023] Figure 1 This is a schematic diagram of the structure of the power cable obtained in Example 1; Figure 2 The results are the infrared spectra of the modified polyolefin granules and polyolefin granules prepared in Example 1.
[0024] In the diagram: 1. Conductor; 2. Fire-resistant layer; 3. Insulation layer; 4. Environmentally friendly filler material layer; 5. Cable wrapping layer; 6. Inner lining layer; 7. Armor layer; 8. Outer sheath one; 9. Outer sheath two. Detailed Implementation
[0025] To make the objectives, technical solutions, and advantages of the present invention clearer, the technical solutions of the present invention will be further described in detail below with reference to specific embodiments: Conductor 1 has a diameter of 10mm, fire-resistant layer 2 has a thickness of 0.13mm, insulation layer 3 has a thickness of 1.8mm, cable wrapping layer 5 has a thickness of 0.14mm, inner lining layer 6 has a thickness of 1.5mm, armor layer 7 has a thickness of 0.25mm, outer sheath 8 has a thickness of 2mm, and outer sheath 9 has a thickness of 0.45mm.
[0026] The mass ratio of alkali-free glass fiber yarn to flame-retardant polypropylene filler rope is 1:1.5.
[0027] Hydrophobic fumed silica (purchased from Fujian Dexingyuan Chemical Co., Ltd., model DXY-757).
[0028] Before adding material granules, the extruder is preheated to the set temperature for 2.5 hours.
[0029] Methods for preparing ceramic silicone rubber granules include: Methyl vinyl silicone rubber was added to a Banbury mixer and mixed in a closed system at 70°C for 2 minutes. Then, hydroxyl silicone oil, silane coupling agent, and zinc borate were added, and mixing continued for 3 minutes. Muscovite powder, kaolin, hydrophobic fumed silica, and glass powder were added in three batches with a 4-minute interval between each batch. The temperature was raised to 150°C, and the mixture was degassed under vacuum at -0.07 MPa for 25 minutes. The mixture was then added to an open mill and passed through it four times. After cooling to room temperature, 2,4-dichlorobenzoyl peroxide was added, and the mixture was re-mixed for 12 minutes. The roller gap was adjusted to 1.2 mm, and flat sheets were continuously produced. The sheets were laid flat and allowed to stand at room temperature for 4 hours. Then, the sheets were cut into strips and fed into a twin-screw granulator. The temperature was 60°C in zone 1, 70°C in zone 2, 75°C in zone 3, and 70°C at the die head. After extrusion, the sheets were cooled with water at 25°C, shaped, and granulated to obtain ceramic silicone rubber granules.
[0030] The ceramic silicone rubber material, by weight, includes: 95 parts methyl vinyl silicone rubber, 30 parts mica powder, 20 parts kaolin, 25 parts hydrophobic fumed silica, 3 parts hydroxyl silicone oil, 0.6 parts silane coupling agent KH-550, 28 parts glass powder, 1 part 2,4-dichlorobenzoyl peroxide, and 4 parts zinc borate.
[0031] Example 1:
[0032] A method for preparing an ultra-thin extruded nylon sheath power cable includes: Step 1: Preheat conductor 1 to 60℃ for 30 minutes, then feed it into the extruder head. Add ceramic silicone rubber granules into the extruder. The milling temperature is: Zone 1 45℃, Zone 2 60℃, Zone 3 80℃. The extruder head temperature is: Zone 4 75℃, Zone 5 80℃. Then extrude it onto the conductor and immediately feed it into the hot air vulcanization tunnel. Hold it at 115℃ for 35 seconds, at 155℃ for 55 seconds, and at 195℃ for 25 seconds. Use three-stage warm water cooling: the first stage cooling water temperature is 60℃, the second stage cooling water temperature is 40℃, and the third stage cooling water temperature is 20℃ to obtain conductor 1 with refractory layer 2. Step 2: Treat the polyvinyl chloride granules at 65℃ for 4 hours, then add them to the extruder. The processing temperatures in the extruder chamber are: Zone 1 145℃, Zone 2 165℃, Zone 3 170℃, Zone 4 173℃, Zone 5 175℃; the flange zone 6 temperature is 175℃; and the die head processing temperatures are: Zone 7 175℃, Zone 8 175℃, Zone 9 175℃, Zone 10 175℃. Extrude the refractory layer and use a three-stage warm water cooling system: the first stage cooling water temperature is 60℃, the second stage cooling water temperature is 40℃, and the third stage cooling water temperature is 20℃ to obtain the insulating inner core. Step 3: Twist the four insulating cores together, wrap the twisted insulating cores with aramid braided fabric to form a cable wrapping layer 5, and then fill the space between the insulating cores and the cable wrapping layer 5 with a mixture of alkali-free glass fiber yarn and flame-retardant polypropylene filler rope to form an environmentally friendly filler material layer 4. Step 4, Inner Liner 6, involves drying modified polyolefin granules at 65℃ for 6 hours, then adding the granules to an extruder. The milling temperatures are: Zone 1 155℃, Zone 2 175℃, Zone 3 188℃, Zone 4 198℃, Zone 5 208℃; Flange Zone 6 temperature is 208℃; and Die Head processing temperatures are: Zone 7 218℃, Zone 8 228℃, Zone 9 228℃, Zone 10 228℃. The material is then extruded onto the cable wrapping layer, using a three-stage warm water cooling system: the first stage cooling water temperature is 60℃, the second stage cooling water temperature is 40℃, and the third stage cooling water temperature is 20℃. Step 5: Wrap two layers of galvanized steel strips around the inner lining layer 6 to form a steel strip armor layer 7. Then, dry the modified polyolefin granules at 65℃ for 4 hours. Then, add the granules to the extruder. The machining temperatures of the extruder chamber are: Zone 1 155℃, Zone 2 175℃, Zone 3 188℃, Zone 4 198℃, Zone 5 208℃. The flange zone 6 temperature is 208℃. The die head machining temperatures are: Zone 7 218℃, Zone 8 228℃, Zone 9 228℃, Zone 10 228℃. Extrude the material onto the armor layer 7 and use a three-stage warm water cooling system: the first stage cooling water temperature is 60℃, the second stage cooling water temperature is 40℃, and the third stage cooling water temperature is 20℃. The traction speed is uniform throughout the cooling process, with a speed range of 20m / min. Step Six: Dry the nylon granules at 80℃ and 0.1MPa vacuum for 6 hours; then add the granules to an SJ-150 extruder with a length-to-diameter ratio of 20:1 and a compression ratio of 3.5:1. The milling temperatures are: Zone 1 234℃, Zone 2 239℃, Zone 3 239℃, Zone 4 244℃, Zone 5 244℃, Zone 6 249℃; the flange zone 7 temperature is 249℃; and the die head processing temperatures are: Zone 8 254℃, Zone 9 254℃, Zone 10 254℃, Zone 11 254℃. After extruding onto the outer sheath (section 8), the material passes through a 1m air-cooling section, followed by three-stage warm water cooling: the first stage cooling water temperature is 60℃, the second stage cooling water temperature is 40℃, and the third stage cooling water temperature is 20℃, thus producing an ultra-thin extruded nylon sheathed power cable.
[0033] A method for preparing modified polyolefin granules, comprising: Polyolefin granules were dried at 28℃ for 2.5 hours and then fed into a twin-screw extruder. A mixture of 1,2-epoxy-4-vinylcyclohexane and dicumyl peroxide was added to the polyolefin granules for a melt grafting reaction. The temperatures were 70℃ in zone one, 115℃ in zone two, 115℃ in zone three, 138℃ at the die head, and 140 r / min at the screw speed. The extrudate was cooled in a cooling water bath, granulated, and then subjected to Soxhlet extraction for 20 hours, followed by vacuum drying to obtain modified polyolefin granules. The mass ratio of the polyolefin granules to 1,2-epoxy-4-vinylcyclohexane was 1:0.1; the mass ratio of the polyolefin granules to dicumyl peroxide was 1:0.008.
[0034] Example 2:
[0035] A method for preparing an ultra-thin extruded nylon sheath power cable includes: Step 1: Preheat conductor 1 to 90℃ for 20 minutes, then feed it into the extruder head. Add ceramic silicone rubber granules into the extruder. The milling temperature is: Zone 1 55℃, Zone 2 75℃, Zone 3 85℃. The extruder head temperature is: Zone 4 80℃, Zone 5 85℃. Then extrude it onto the conductor and immediately feed it into the hot air vulcanization tunnel. Hold it at 125℃ for 25 seconds, at 165℃ for 45 seconds, and at 205℃ for 15 seconds. Use three-stage warm water cooling: the first stage cooling water temperature is 80℃, the second stage cooling water temperature is 50℃, and the third stage cooling water temperature is 30℃ to obtain conductor 1 with refractory layer 2. Step 2: Treat the polyvinyl chloride granules at 70℃ for 3 hours, then add them to the extruder. The processing temperatures in the extruder chamber are: Zone 1 145℃, Zone 2 165℃, Zone 3 170℃, Zone 4 173℃, Zone 5 175℃; the flange zone 6 temperature is 175℃; and the die head processing temperatures are: Zone 7 175℃, Zone 8 175℃, Zone 9 175℃, Zone 10 175℃. Extrude the refractory layer 2 and use a three-stage warm water cooling system: the first stage cooling water temperature is 80℃, the second stage cooling water temperature is 50℃, and the third stage cooling water temperature is 30℃ to obtain the insulating inner core. Step 3: Twist the four insulating cores together, wrap the twisted insulating cores with aramid braided fabric to form a cable wrapping layer 5, and then fill the space between the insulating cores and the cable wrapping layer 5 with a mixture of alkali-free glass fiber yarn and flame-retardant polypropylene filler rope to form an environmentally friendly filler material layer 4. Step 4: The inner lining layer 6 is made by drying modified polyolefin granules at 75℃ for 4 hours, and then adding the granules into an extruder. The milling temperatures are: Zone 1 165℃, Zone 2 185℃, Zone 3 192℃, Zone 4 202℃, Zone 5 212℃, Flange Zone 6 212℃, and Die Head Temperatures are: Zone 7 222℃, Zone 8 233℃, Zone 9 233℃, Zone 10 233℃. Then it is extruded onto the cable wrapping layer 5, using a three-stage warm water cooling system: the first stage cooling water temperature is 80℃, the second stage cooling water temperature is 50℃, and the third stage cooling water temperature is 30℃. Step 5: Wrap two layers of galvanized steel strips around the inner lining layer 6 to form a steel strip armor layer 7. Then, dry the modified polyolefin granules at 75℃ for 4 hours. Then, add the granules to the extruder. The machining temperatures of the extruder chamber are: Zone 1 165℃, Zone 2 185℃, Zone 3 192℃, Zone 4 202℃, Zone 5 212℃. The flange zone 6 temperature is 212℃. The die head machining temperatures are: Zone 7 222℃, Zone 8 233℃, Zone 9 233℃, Zone 10 233℃. Extrude the material onto the armor layer 7 and use a three-stage warm water cooling system: the first stage cooling water temperature is 80℃, the second stage cooling water temperature is 50℃, and the third stage cooling water temperature is 30℃. The traction speed is uniform throughout the cooling process, with a speed range of 20m / min. Step Six: Dry the nylon granules at 105℃ and 0.05MPa vacuum for 4 hours; then add the granules to an SJ-120 extruder with a length-to-diameter ratio of 25:1 and a compression ratio of 4:1. The milling temperatures are: Zone 1 236℃, Zone 2 241℃, Zone 3 241℃, Zone 4 246℃, Zone 5 246℃, Zone 6 251℃; the flange zone 7 temperature is 251℃; and the die head processing temperatures are: Zone 8 256℃, Zone 9 256℃, Zone 10 256℃, Zone 11 256℃. After extruding onto the outer sheath (section 8), the material passes through a 1m air-cooling section, followed by three-stage warm water cooling: the first stage cooling water temperature is 80℃, the second stage cooling water temperature is 50℃, and the third stage cooling water temperature is 30℃, thus producing an ultra-thin extruded nylon sheath power cable.
[0036] A method for preparing modified polyolefin granules, comprising: Polyolefin granules were dried at 35℃ for 2.5 hours and then fed into a twin-screw extruder. A mixture of 1,2-epoxy-4-vinylcyclohexane and dicumyl peroxide was added to the polyolefin granules for melt grafting. The temperatures were 75℃ in zone one, 125℃ in zone two, 125℃ in zone three, 145℃ at the die head, and 130 r / min at the screw speed. The extrudate was cooled in a cooling water bath, granulated, and then subjected to Soxhlet extraction for 24 hours, followed by vacuum drying to obtain modified polyolefin granules. The mass ratio of the polyolefin granules to 1,2-epoxy-4-vinylcyclohexane was 1:0.15; the mass ratio of the polyolefin granules to dicumyl peroxide was 1:0.013.
[0037] Example 3:
[0038] A method for preparing an ultra-thin extruded nylon sheath power cable includes: Step 1: Preheat conductor 1 to 70℃ for 25 minutes, then feed it into the extruder head. Add ceramic silicone rubber granules into the extruder. The milling temperature is: Zone 1 50℃, Zone 2 65℃, Zone 3 82℃. The extruder head temperature is: Zone 4 78℃, Zone 5 82℃. Then extrude it onto the conductor and immediately feed it into the hot air vulcanization tunnel. Hold it at 120℃ for 30 seconds, at 160℃ for 50 seconds, and at 200℃ for 20 seconds. Use three-stage warm water cooling: the first stage cooling water temperature is 70℃, the second stage cooling water temperature is 45℃, and the third stage cooling water temperature is 25℃ to obtain conductor 1 with refractory layer 2. Step 2: Treat the polyvinyl chloride granules at 68℃ for 3.5 hours, then add them to the extruder. The processing temperatures in the extruder chamber are: Zone 1 145℃, Zone 2 165℃, Zone 3 170℃, Zone 4 173℃, Zone 5 175℃; the flange zone 6 temperature is 175℃; and the die head processing temperatures are: Zone 7 175℃, Zone 8 175℃, Zone 9 175℃, Zone 10 175℃. Extrude the refractory layer 2 and use a three-stage warm water cooling system: the first stage cooling water temperature is 70℃, the second stage cooling water temperature is 45℃, and the third stage cooling water temperature is 25℃ to obtain the insulating inner core. Step 3: Twist the four insulating cores together, wrap the twisted insulating cores with aramid braided fabric to form a cable wrapping layer 5, and then fill the space between the insulating cores and the cable wrapping layer 5 with a mixture of alkali-free glass fiber yarn and flame-retardant polypropylene filler rope to form an environmentally friendly filler material layer 4. Step 4, Inner Liner 6, involves drying modified polyolefin granules at 70℃ for 5 hours, then adding the granules to an extruder. The milling temperatures are: Zone 1 160℃, Zone 2 180℃, Zone 3 190℃, Zone 4 200℃, Zone 5 210℃; Flange Zone 6 temperature is 210℃; and Die Head processing temperatures are: Zone 7 220℃, Zone 8 230℃, Zone 9 230℃, Zone 10 230℃. The material is then extruded onto the cable wrapping layer, using a three-stage warm water cooling system: the first stage cooling water temperature is 70℃, the second stage cooling water temperature is 45℃, and the third stage cooling water temperature is 25℃. Step 5: Wrap two layers of galvanized steel strips around the inner lining layer 6 to form a steel strip armor layer 7. Then, dry the modified polyolefin granules at 70℃ for 5 hours. Then, add the granules to the extruder. The machining temperatures of the extruder chamber are: Zone 1 160℃, Zone 2 180℃, Zone 3 190℃, Zone 4 200℃, Zone 5 210℃. The flange zone 6 temperature is 210℃. The die head machining temperatures are: Zone 7 220℃, Zone 8 230℃, Zone 9 230℃, Zone 10 230℃. Extrude the material onto the armor layer 7 and use a three-stage warm water cooling system: the first stage cooling water temperature is 70℃, the second stage cooling water temperature is 45℃, and the third stage cooling water temperature is 25℃. The traction speed is uniform throughout the cooling process, with a speed range of 20m / min. Step Six: Dry the nylon granules at 100℃ and 0.08MPa vacuum for 5 hours; then add the granules to an SJ-120 extruder with a length-to-diameter ratio of 20:1 and a compression ratio of 3.5:1. The machining temperatures in the die chamber are: Zone 1 235℃, Zone 2 240℃, Zone 3 240℃, Zone 4 245℃, Zone 5 245℃, Zone 6 250℃; the flange zone 7 temperature is 250℃; and the die head machining temperatures are: Zone 8 255℃, Zone 9 255℃, Zone 10 255℃, Zone 11 255℃. After extruding onto the outer sheath (section 8), the material passes through a 1m air-cooling section, followed by three-stage warm water cooling: the first stage cooling water temperature is 70℃, the second stage cooling water temperature is 45℃, and the third stage cooling water temperature is 25℃, thus producing an ultra-thin extruded nylon sheath power cable.
[0039] A method for preparing modified polyolefin granules, comprising: Polyolefin granules were dried at 30℃ for 3 hours and then fed into a twin-screw extruder. A uniform mixture of 1,2-epoxy-4-vinylcyclohexane and dicumyl peroxide was added to the polyolefin granules for melt grafting. The temperatures were 72℃ in zone one, 120℃ in zone two, 120℃ in zone three, 140℃ at the die head, and 135 r / min at the screw speed. The extrudate was cooled in a cooling water bath, granulated, and then subjected to Soxhlet extraction for 22 hours, followed by vacuum drying to obtain modified polyolefin granules. The mass ratio of the polyolefin granules to 1,2-epoxy-4-vinylcyclohexane was 1:0.13; the mass ratio of the polyolefin granules to dicumyl peroxide was 1:0.01.
[0040] Comparative Example 1: The difference between the preparation method of an ultra-thin extruded nylon sheath power cable and Example 1 is that polyolefin granules are used instead of modified polyolefin granules.
[0041] Comparative Example 2: The difference between the preparation method of an ultra-thin extruded nylon sheath power cable and Example 1 is that a 25°C water temperature is used for cooling, replacing the three-stage warm water cooling.
[0042] Comparative Example 3: The difference between the preparation method of an ultra-thin extruded nylon sheath power cable and Example 1 is that the dwell temperature in the hot air vulcanization oven in step one is 180°C and the dwell time is 115s.
[0043] Performance testing 1. Infrared spectroscopy test Infrared spectroscopy was performed using a Fourier transform infrared spectrometer and the potassium bromide pellet method.
[0044] The modified polyolefin pellets and polyolefin pellets prepared in Example 1 were subjected to the above tests, and the results are as follows: Figure 2 As shown. By Figure 2It can be seen that, compared with the infrared spectrum of polyolefin particles, the infrared spectrum of modified polyolefin particles is at 1239 cm⁻¹. -1 915cm -1 The presence of infrared characteristic absorption peaks of epoxy groups indicates that 1,2-epoxy-4-vinylcyclohexane participated in the formation reaction of modified polyolefin particles.
[0045] 2. Tensile property test Tensile properties were tested according to GB / T1040.2-2022. The sample length was 170 mm, the tensile rate was 2 mm / min, the test temperature was -40℃, and the holding time was 4 h.
[0046] Table 1 Tensile property test results
[0047] The power cables prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to the above tests, and the results are shown in Table 1. Table 1 shows that the samples prepared using modified polyolefin granules and a three-stage warm water cooling process exhibited significantly better tensile strength retention than the comparative samples. This is mainly attributed to two aspects: firstly, the chemically grafted epoxy polar groups enhance the interaction forces between polyolefin molecular chains, enabling the material to maintain a tight entangled network structure even at low temperatures, thus improving its resistance to chain slippage and microcrack propagation under external tensile forces; secondly, the gradient warm water cooling method avoids the large-size spherulites and internal micropore defects caused by traditional rapid cooling processes, resulting in a finer and more uniform sheath crystallization and a more moderate internal stress distribution. In contrast, unmodified polyolefins performed weaker due to the lack of a polar reinforcement mechanism, while samples with single cold water cooling or improper vulcanization showed further deterioration in low-temperature tensile properties due to internal defects and structural inhomogeneity.
[0048] 3. Impact strength test The notched impact strength of the cantilever beam was tested according to GB / T1843-2008 at a test temperature of -20℃.
[0049] Table 2. Results of Notched Impact Strength Test of Cantilever Beam
[0050] The power cables prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to the above tests, and the results are shown in Table 2. Table 2 shows that the low-temperature cantilever beam notched impact strength test results demonstrate a significant synergistic enhancement effect of the modification process and the cooling regime. The epoxy side groups introduced into the modified polyolefin can effectively induce a large number of crazes and shear deformation bands in the matrix under high-speed impact. These micro-deformation regions can dissipate a large amount of external impact energy, delaying the rapid propagation of cracks. Simultaneously, the three-stage warm water cooling optimizes the crystallinity and wafer thickness distribution of each cross-section of the sheath, avoiding localized brittle zones caused by excessive temperature differences between the inner and outer layers, thus forming a more effective plastic deformation buffer layer at the notch tip. In the comparative examples, the unmodified samples lacked an energy dissipation mechanism, the samples cooled only by cold water experienced quenching embrittlement, and the samples with improper vulcanization processes exhibited significantly lower impact resistance due to uneven cross-linking networks.
[0051] The conventional techniques described in the above embodiments are existing technologies known to those skilled in the art, and therefore will not be described in detail here.
[0052] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.
Claims
1. A power cable with an ultra-thin extruded nylon sheath, characterized in that: The power cable contains four insulating cores, each of which includes, from the inside out, a conductor (1), a fire-resistant layer (2), and an insulation layer (3); the insulating cores are all embedded in an environmentally friendly filling material layer (4), and a cable wrapping layer (5) is wrapped around the insulating cores and the environmentally friendly filling material layer (4); the cable wrapping layer (5) is covered from the inside out with an inner lining layer (6), an armor layer (7), an outer sheath layer one (8), and an outer sheath layer two (9).
2. The ultra-thin extruded nylon sheath power cable according to claim 1, characterized in that: The environmentally friendly filler material layer (4) is formed by twisting four insulating cores together, wrapping the twisted insulating cores with aramid braided cloth to form a cable wrapping layer (5), and then filling the space between the insulating cores and the cable wrapping layer (5) with a mixture of alkali-free glass fiber yarn and flame-retardant polypropylene filler rope to form the environmentally friendly filler material layer (4).
3. The ultra-thin extruded nylon sheath power cable according to claim 1, characterized in that: The conductor (1) has a diameter of 1.13-34 mm, the fire-resistant layer (2) has a thickness of 0.1-0.16 mm, the insulation layer (3) has a thickness of 0.7-3 mm, the cable wrapping layer (5) has a thickness of 0.1-0.18 mm, the inner lining layer (6) has a thickness of 1-2 mm, the armor layer (7) has a thickness of 0.2-0.8 mm, the outer sheath layer one (8) has a thickness of 1.4-3 mm, and the outer sheath layer two (9) has a thickness of 0.3-0.6 mm.
4. The ultra-thin extruded nylon sheath power cable according to claim 1, characterized in that: The preparation method of the second outer protective layer includes: drying nylon granules at 80-105℃ and 0.05-0.1MPa vacuum for 4-6 hours; then adding the granules to an SJ-120 or SJ-150 extruder with a length-to-diameter ratio of 20:1-25:1 and a compression ratio of 3.5:1-4:1, and machining temperatures of: Zone 1 234-236℃, Zone 2 239-241℃, and Zone 3 239-241℃. The temperatures are as follows: Zone 4: 244-246℃, Zone 5: 244-246℃, Zone 6: 249-251℃, Zone 7: 249-251℃, and the machining temperature of the machine head is: Zone 8: 254-256℃, Zone 9: 254-256℃, Zone 10: 254-256℃, Zone 11: 254-256℃. After being extruded onto the first outer protective layer, it passes through a 0.5-1.5m air cooling section, and then undergoes three-stage warm water cooling and shaping to obtain the second outer protective layer.
5. The ultra-thin extruded nylon sheath power cable according to claim 4, characterized in that: The three-stage warm water cooling system includes: a first stage with a cooling water temperature of 60-80℃, a second stage with a cooling water temperature of 40-50℃, and a third stage with a cooling water temperature of 20-30℃.
6. The ultra-thin extruded nylon sheath power cable according to claim 4, characterized in that: Before adding the granules, the extruder needs to be preheated to the set temperature for 2-2.5 hours.
7. The ultra-thin extruded nylon sheath power cable according to claim 1, characterized in that: The conductor (1) is selected from one of copper core conductor, aluminum core conductor or aluminum alloy core conductor; The refractory layer (2) includes a ceramic silicone rubber refractory layer; the ceramic silicone rubber refractory layer is prepared by melting and extruding ceramic silicone rubber particles, vulcanizing them, and then cooling and shaping them. The insulating layer (3) is selected from either polyvinyl chloride insulating layer or cross-linked polyethylene insulating layer; The inner liner (6) and the outer sheath (8) are both selected from either polyolefin sheaths or modified polyolefin sheaths; the modified polyolefin sheath is prepared by melt extrusion of modified polyolefin granules and then cooling and shaping. The armor layer (7) includes a steel strip armor layer; The outer protective layer two (9) includes an ultra-thin nylon sheath.
8. The ultra-thin extruded nylon sheath power cable according to claim 7, characterized in that: The ceramic silicone rubber granules, by weight, comprise: 95-105 parts methyl vinyl silicone rubber, 30-50 parts mica powder, 20-40 parts kaolin, 25-30 parts hydrophobic fumed silica, 3-5 parts hydroxyl silicone oil, 0.6-1 part silane coupling agent, 28-32 parts glass powder, 1-1.4 parts 2,4-dichlorobenzoyl peroxide, and 4-6 parts zinc borate.
9. The ultra-thin extruded nylon sheath power cable according to claim 7, characterized in that: The method for preparing the modified polyolefin granules includes: The polyolefin granules were dried at 28-35℃ for 2.5-4 hours and then fed into a twin-screw extruder. 1,2-epoxy-4-vinylcyclohexane and diisopropylbenzene peroxide were mixed evenly and then added to the polyolefin granules for melt grafting reaction. The temperature of zone 1 was 70-75℃, zone 2 was 115-125℃, zone 3 was 115-125℃, the die head temperature was 138-145℃, and the screw speed was 130-140 r / min. After the extrudate was cooled in a cooling water tank, it was pelletized and then subjected to Soxhlet extraction for 20-24 hours. After vacuum drying, the modified polyolefin granules were obtained.
10. The ultra-thin extruded nylon sheath power cable according to claim 9, characterized in that: The mass ratio of the polyolefin granules to 1,2-epoxy-4-vinylcyclohexane is 1:0.1-0.15; the mass ratio of the polyolefin granules to dicumyl peroxide is 1:0.008-0.013.